Educação infantil e ensino fundamental: relações em construção - Ana Cláudia Figueiredo Brasil Silva Melo (2021)
Kindergarten and Elementary Education are educational stages with different identities and constitution processes that produce different conceptions, ways of pedagogically relating to childhood, different teaching and school cultures. This research aimed to analyze the impacts on the conceptions, organization and functioning of both stages in the context of the reopening of Kindergarten classes in public schools in Belo Horizonte that exclusively attended Elementary School. The theoretical foundation was built and the data analyzed in dialogue with the fields of Social Studies of Childhood, Childhood Pedagogies, School Cultures and, above all, with academic research that investigated the relationships and transitions between the first two stages of Basic Education (BARBOSA, 2006; CAMPOS, 2010; FORMOSINHO, 2016; KRAMER, 2006; OLIVEIRA-FORMOSINHO, 2008; MOTTA, 2010; NEVES, 2010; SARMENTO, 2005, among others). The field work was carried out in two stages. The first of them took place at a school in the Municipal Education Network of Belo Horizonte and involved participant observations and semi-structured interviews in a final Kindergarten class and an initial Elementary School class. The second stage of the work, which took place during the period of in-person suspension from school activities due to the Covid-19 pandemic, involved remote press conferences with teachers and pedagogical coordinators representing thirteen different schools. Data analysis revealed a wide range and diversity of scenarios generated by the coexistence of the two stages in the same school. Two aspects emerged: the humanization of school practices when they began to focus on children and the tension between this pedagogical logic and the content and transmission logic. Within the scope of the coexistence of the two stages in the same school, the possibilities for knowledge between them were also highlighted, especially in Elementary School in relation to Early Childhood Education; the tensions between childhood cultures and school cultures; possibilities of expression of family and community ties between children from Kindergarten and children and teenagers from Elementary School, in the school space; and the emergence of a way of being and acting permeated by care, on the part of adults and also children and adolescents in Elementary School, from the arrival of small children.